Marketing Strategies to Increase Sales (Case Study: Es Cendol SMEs in Sukarame District, Bandar Lampung) - Alfitroni, Ahmad Sadam; Purnomo, Agus (International Publisher, 2026)
This study aims to analyze the marketing strategies implemented by UMKM Es Cendol Ibu Sri in increasing sales in Sukarame District, Bandar Lampung City. This research employs a descriptive qualitative approach using a case study method. Data collection was carried out through in-depth interviews, direct observation, and documentation. The research informants consisted of the owner of UMKM Es Cendol Ibu Sri as the key informant, employees, customers, and related parties. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, using source and method triangulation to ensure the validity and reliability of the research data. The results show that the marketing strategy of UMKM Es Cendol Ibu Sri is still dominated by conventional methods, such as word-of-mouth promotion and direct sales at the business location. This UMKM has strengths in maintaining product quality, using natural raw materials, offering affordable prices, and providing friendly service. Opportunities for business development are open through the utilization of digital marketing, product and packaging innovation, and a strategic business location, although the business faces threats in the form of intense competition and fluctuations in raw material prices.